Project-Based Learning Approach and Its Impact for the Pancasila Student Profile Strengthening Project - Chika Gianistika (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The purpose of this study is to determine the impact of the project-based learning approach on the implementation of the Pancasila student profile strengthening project. This research uses a qualitative approach. Data collection techniques in this study with; 1) Interview method addressed to the grade 4 teacher of karawang district driving school, 2) Documentation method, and 3) observation method. In this study, it was stated that inthe nature of the project activities to strengthen the profile of pancasila students in addition to fostering the character of the pancasila student profile, students also have good interactions with fellow students and with their teachers. In the implementation of the project carried out, students are required to work together and discuss each other so that there is an in-depth interaction between students in different classes; this has an impact on student socialization which is more diverse and widespread.